Digital Marketing Development Strategy of Sharia Cooperative - Tati Handayani; Sufyati HS; Prima Dwi Priyatno (Garuda Prestasi Nusantara Consulting, 2022)
The development of Sharia Cooperatives faced obstacles due to the Covid-19 pandemic situation. Many people no longer use sharia cooperatives in carrying out their daily lives, especially the owner of business. This situation requires innovation by utilizing digitization technology. One of the form of technology that can be used is digital marketing, with digital marketing communications and transactions can be carried out at any time. This study focuses on mapping the characteristics of Islamic cooperatives and evaluating the performance of Islamic cooperatives as well as producing business strategy models for Islamic cooperatives. The method used is descriptive qualitative with SWOT analysis techniques. Sampling method use non-probability sampling (snowball). The participants in this study were the management of the Baiturrahman Mitra Umat Sharia Consumer Cooperative (KKS), Bojong Gede, Bogor, West Java, totaling 6 informants. The results of the study show that the Baiturrahman Mitra Umat KKS is a cooperative that has a strong and growing market. The Baiturrahman Mitra Umat PSC can carry out two types of strategies, namely intensive strategies and integrative strategies. Intensive strategies can be carried out by cooperatives in the form of market penetration and market and product development. The integrative strategy can be carried out by cooperatives in the form of forward integration, backward integration, and horizontal integration. Keywords: strategy, digital marketing, sharia cooperatives